Emerging Trends and Challenges in Chatbot Technology: A Japanese Industry Perspective - Ismail, Andi Regina Acacia; Fujita, Shunya; Sakamoto, Kenji; Takahashi, Hiroko; Panessai, Ismail Yusuf (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study examines the impact of chatbot technology across various industries, including e-commerce, healthcare, education, banking, and travel, based on interviews and surveys conducted in Japan in March 2024. Using a mixed-methods approach, we analyzed both quantitative survey data and qualitative interview insights. Findings show that 75% of e-commerce businesses experienced a 30% reduction in response times and a 40% increase in user engagement, while healthcare providers saw a 20% decrease in administrative tasks for 65% of respondents, though 25% reported data privacy concerns. Educational institutions achieved a 25% reduction in administrative workload and a 50% boost in student interaction, with 70% of students finding chatbots beneficial. In banking, 80% of institutions realized a 35% reduction in response times, but 30% encountered data security challenges. Travel agencies noted a 40% faster booking process and a 20% decrease in operational costs, benefiting 60% of customers. Despite these advantages, common challenges include integration with legacy systems, data security, and handling complex queries. Recommendations include investing in ongoing improvements, enhancing data privacy measures, and training users. Future research should focus on advanced natural language processing, long-term impacts, and ethical considerations related to chatbot use.